1990
DOI: 10.1007/bf00689087
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy of dacarbazine and fotemustine in disseminated malignant melanoma

Abstract: A total of 70 patients presenting with a disseminated malignant melanoma were entered into a multicentric study of combination chemotherapy using dacarbazine and fotemustine. In all, 63 patients were evaluable, 31.8% of whom had previously received cytotoxic chemotherapy. The protocol consisted of induction treatment with a weekly infusion of 100 mg/m2 fotemustine on days 1 and 8 and a daily infusion of 250 mg/m2 dacarbazine on days 15/18 followed by a 4- to 5-week rest period. Responding and stabilized patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…An OR rate of 12% was observed but the treatment was associated with a 30% grade IV thrombopenia toxicity. It has been observed, in a more recent study of fotemustine 100 mg m-2 in melanoma, that the day 1, day 8 schedule is well tolerated with a similar efficacy (Avril et al, 1990 We report herein a French multicentre phase II study on fotemustine on day 1 and day 8 in patients with poorprognosis advanced NSCLC. …”
mentioning
confidence: 81%
See 2 more Smart Citations
“…An OR rate of 12% was observed but the treatment was associated with a 30% grade IV thrombopenia toxicity. It has been observed, in a more recent study of fotemustine 100 mg m-2 in melanoma, that the day 1, day 8 schedule is well tolerated with a similar efficacy (Avril et al, 1990 We report herein a French multicentre phase II study on fotemustine on day 1 and day 8 in patients with poorprognosis advanced NSCLC. …”
mentioning
confidence: 81%
“…Among NSCLC patients, those who relapse after first-line chemotherapy or those presenting central nervous system metastases are considered to have poor prognosis and are usually ineligible for cisplatin-based therapy. Thus, a search for new drugs is required in an attempt to obtain a survival advantage without inacceptable toxicity, particularly in patients with poor-prognosis NSCLC.Fotemustine, a new amino acid phosphonate derivative of the nitrosourea group, has been recently introduced in the treatment of human solid malignancies (Avril et al, 1990;Jacquillat et al, 1990a). This cytotoxic drug induced a 24% objective response (OR) rate in a phase II study of fotemustine as a single-drug therapy in disseminated malignant melanoma (Jacquillat et al, 1990a), including patients with brain metastases (Jacquillat et al, 1990b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a synergistic effect among the combination of D and F was observed in melanoma cell lines, in patients with disseminated malignant melanoma and recurrent GBM (Fischel et al, 1990;Aamdal et al, 1992;Avril et al, 1990). F, (diethyl 1-(3-(2 chloroethyl) 3 nitrosoureido) ethyl phosphonate) is an alkylating agent characterised by the grafting of a phosphonoalanine group onto the nitrosourea radical with consequent high lipophilia and a high brain permeability coefficient.…”
mentioning
confidence: 99%
“…In most of these trials, only 10~20% response rates were observed. There was little evidence to suggest superiority of these combinations compared with DTIC treatment alone (31)(32)(33).…”
Section: Chemotherapy Drug Combinationsmentioning
confidence: 99%